Experimental techniques for the characterization of carbon nanoparticles – a brief overview - Kempiński, Wojciech; Łoś, Szymon; Kempiński, Mateusz; Markowski, Damian (Beilstein Journal of Nanotechnology, 2014)
The review of four experimental methods: X-ray diffraction, Raman spectroscopy, electron paramagnetic resonance and four-point electrical conductivity measurements is presented to characterize carbon nanoparticles. Two types of carbon nanoparticle systems are discussed: one comprising the powder of individual carbon nanoparticles and the second as a structurally interconnected nanoparticle matrix in the form of a fiber. X-ray diffraction and Raman spectroscopy reveal the atomic structure of the carbon nanoparticles and allow for observation of the changes in the quasi-graphitic ordering induced by ultrasonic irradiation and with the so-called quasi-high pressure effect under adsorption conditions. Structural changes have strong influence on the electronic properties, especially the localization of charge carriers within the nanoparticles, which can be observed with the EPR technique. This in turn can be well-correlated with the four-point electrical conductivity measurements which directly show the character of the charge carrier transport within the examined structures.
Keywords: carbon nanoparticles; charge carrier transport; host–guest interactions; spin localization